A robust binary supramolecular organic framework (SOF) with high CO2 adsorption and selectivity - Lu, Jian; Perez-Krap, Cristina; Suyetin, Mikhail; Alsmail, Nada H.; Yan, Yong; Yang, Sihai; Lewis, William; Bichoutskaia, Elena; Tang, Chiu C.; Blake, Alexander J.; Cao, Rong; Schröder, Martin (American Chemical Society, 2014)
A robust binary hydrogen-bonded supramolecular organic framework (SOF-7) has been synthesized by solvothermal reaction of 1,4-bis-(4-(3,5-dicyano-2,6 dipyridyl)dihydropyridyl)benzene (1) and 5,5’-bis-(azanediyl)-oxalyl-diisophthalic acid (2). Single crystal X-ray diffraction analysis shows that SOF-7 comprises 2 and 1,4-bis-(4-(3,5-dicyano-2,6-dipyridyl)pyridyl)benzene (3), the latter formed in situ from the oxidative dehydrogenation of 1. SOF-7 shows a three-dimensional four-fold interpenetrat-ed structure with complementary O−H···N hydrogen bonds to form channels that are decorated with cyano- and amide-groups. SOF-7 exhibits excellent thermal stability and sol-vent and moisture durability, as well as permanent porosity. The activated desolvated material SOF-7a shows high CO2 sorption capacity and selectivity compared with other po-rous organic materials assembled solely through hydrogen bonding.